Bilateral video-assisted thoracic surgery for esophageal cancer with left inferior pulmonary vein invasion following chemoradiation therapy - Masakazu Fujii; Naoya Okada; Hiroaki Kato; Satoshi Ishihara; Masaru Abe; Takumi Yamabuki; Kentaro Kato; Minoru Takada; Yoshiyasu Ambo; Takeshi Yokoyama; Yoshihiro Kinoshita (Surgical Case Reports)
Abstract Background The surgical strategy for thoracic esophageal cancer that invades the lungs is controversial. In particular, invasion of the pulmonary vein is often regarded unresectable. We successfully applied bilateral video-assisted thoracic surgery (VATS) in esophagectomy for esophageal cancer with left inferior pulmonary vein invasion following induction chemoradiotherapy (CRT), with a favorable response. Case presentation A 64-year-old woman was diagnosed with squamous cell carcinoma of the lower third of the esophagus. Computed tomography (CT) revealed that the tumor was suspected to be invading the main trunk of the left lower pulmonary vein and left lower lung. We initiated induction CRT comprising 5-fluorouracil, cisplatin, and concurrent radiotherapy at 50.4 Gy/28Fr. CT revealed shrinkage of the tumor, and the main trunk of the left inferior pulmonary vein was released from the tumor invasion. We considered the tumor to be completely resectable. VATS esophagectomy is usually performed using a right-sided approach. However, the right-sided approach is inappropriate for evaluating tumors around the left inferior pulmonary vein. We started with left-sided VATS to determine tumor resectability and dissected between the esophagus and the main trunk of the left inferior pulmonary vein. We only needed to perform partial resection of the left lower lobe. We then performed a right-sided VATS esophagectomy and lymphadenectomy with partial en bloc resection of the left lower lobe. Following this, we performed hand-assisted laparoscopic proximal gastrectomy and reconstruction using the gastric remnant. The postoperative course was uneventful. The patient was discharged on postoperative day 14. Histopathological examination of the surgical specimen revealed a complete pathological response without any remnant tumor or lymph node metastasis. There were no signs of recurrence or metastasis at the 1-year follow-up. Conclusions Curative resection for thoracic esophageal cancer that invades the pulmonary vein could be possible via the bilateral VATS approach following induction CRT with a favorable response.